Bertrand-Edgeworth competition with substantial product differentiation - Robert Somogyi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
Since Kreps and Scheinkman's seminal article (1983) a large number of papers have analyzed capacity constraints' potential to relax price competition. However, the ensuing literature has assumed that products are either perfect or very close substitutes. Therefore none of the papers has investigated the interaction between capacity constraints and substantial local monopoly power. The aim of the present paper is to shed light on this question using a standard Hotelling setup. The high level of product dfferentiation results in a variety of equilibrium firm behavior and it generates at least one pure strategy equilibrium for any capacity level. Thus the presence of local monopoly power challenges one of the most general findings about Bertrand-Edgeworth competition: the non-existence of pure strategy equilibria for some capacity levels.
Keywords: D21; D43; L13; 330; Duopoly; Bertrand-Edgeworth competition; Hotelling; Capacity constraint